Frequency and Implications of Concurrent Complications Following Adult Spinal Deformity Corrective Surgery. Issue 21 (1st November 2021) - Bortz, Cole; Pierce, Katherine E.; Brown, Avery; Alas, Haddy; Passfall, Lara; Krol, Oscar; Kummer, Nicholas A.; Wang, Erik; O'Connell, Brooke; Wang, Charles; Vasquez-Montes, Dennis; Diebo, Bassel G.; et al.
Abstract : Supplemental Digital Content is available in the text This study assesses common complication co-occurrences following adult spinal deformity-corrective surgery. Body systems most commonly affected by complication co-occurrences were pulmonary and cardiovascular; common co-occurrences included reintubation/prolonged ventilator use and pulmonary embolism/deep vein thrombosis. Surgical factors like operative time ≥400 minutes and fusion ≥9 levels were most strongly associated with complication co-occurrence. Abstract : Study Design: Retrospective review. Objective: Identify co-occurring perioperative complications and associated predictors in a population of patients undergoing surgery for adult spinal deformity (ASD). Summary of Background Data: Few studies have investigated the development of multiple, co-occurring complications following ASD-corrective surgery. Preoperative risk stratification may benefit from identification of factors associated with multiple, co-occurring complications. Methods: Elective ASD patients in National Surgical Quality Improvement Program (NSQIP) 2005 to 2016 were isolated; rates of co-occurring complications and affected body systems were assessed via cross tabulation. Random forest analysis identified top patient and surgical factors associated with complication co-occurrence, using conditional inference trees to identify significant cutoff points. Binary logistic regression indicated effect size of top influential factors associated with complication co-occurrence at each factor's respective cutoff point. Results: Included: 6486 ASD patients. The overall perioperative complication rate was 34.8%; 28.5% of patients experienced one complication, 4.5% experienced two, and 1.8% experienced 3+. Overall, 11% of complication co-occurrences were pulmonary/cardiovascular, 9% pulmonary/renal, and 4% integumentary/renal. By complication type, the most common co-occurrences were transfusion/urinary tract infection (UTI) (24.3%) and transfusion/pneumonia (17.7%). Surgical factors of operative time ≥400 minutes and fusion ≥9 levels were the strongest factors associated with the incidence of co-occurring complications, followed by patient-specific variables like American Society of Anesthesiologists (ASA) physical status classification grade ≥2 and age ≥65 years. Regression analysis further showed associations between increasing complication number and longer length of stay (LOS), ( R 2  = 0.202, P  < 0.001), non-home discharge ( R 2  = 0.111, P  = 0.001), and readmission ( R 2  = 0.010, P  < 0.001). Conclusion: For surgical ASD patients, the overall rate of co-occurring perioperative complications was 6.3%. Body systems most commonly affected by complication co-occurrences were pulmonary and cardiovascular, and common co-occurrences included transfusion/UTI (24.3%) and transfusion/pneumonia (17.7%). Increasing number of perioperative complications was associated with greater LOS, non-home discharge, and readmission, highlighting the importance of identifying risk factors for complication co-occurrences. Level of Evidence: 3